Simultaneous Supplementation of Bacillus subtilis and Antibiotic Growth Promoters by Stages Improved Intestinal Function of Pullets by Altering Gut Microbiota - Li, Xueyuan; Wu, Shengru; Li, Xinyi; Yan, Tao; Duan, Yongle; Yang, Xin; Duan, Yulan; Sun, Qingzhu; Yang, Xiaojun (Frontiers in Microbiology, 2018)
Early nutrition of pullets could determine the overall development and the performance of laying hens. With the aim to reduce the use of antibiotic growth promoters (AGPs) and to maintain the growth and development of pullets, the effect of simultaneous short-termed supplementation of AGPs (bacitracin zinc 20 mg/kg and colistin sulfate 4 mg/kg) and Bacillus subtilis (B. subtilis) DSM17299 probiotic, as well as the effect of supplementation of AGPs (bacitracin zinc 20 mg/kg and colistin sulfate 4 mg/kg) during the whole period (0~16 weeks) on the overall growth and development, intestinal health, and caecal microbiota of pullets were evaluated. In the present study, a total of 630 one-day-old Hy-Line Brown layers were randomly distributed into five equal groups: including the AGPs group (supplemented with AGPs based on basal diets for 16 weeks), the BA3 group (supplemented with AGPs and B. subtilis based on basal diets for 3 weeks), the BA6 group (for 6 weeks), the BA12 group (for 12 weeks), and the BA16 group (for 16 weeks). When compared with the AGPs group, the supplementation of AGPs + B. subtilis for the first 3 weeks could maintain overall growth performance, including the average body weight, average feed intake, average daily weight gain, and feed conversion ratio of pullets at 3, 6, 12, and 16 weeks of age (P > 0.05). Meanwhile, the characteristic growth indexes in different periods were separately measured. At 3 weeks of age, the amylase activity in ileum was elevated (P = 0.028), and the length of tibia was up to the standard in the BA3 group. At 12 weeks of age, the increased villus height (P = 0.046) of jejunum, increased villus height (P = 0.023) and ratio of villus height to crypt depth (P = 0.012) of ileum, decreased crypt depth (P = 0.002) of ileum, and elevated mRNA levels of sucrase in jejunum (P < 0.05) were all identified in the BA3 group. At 16 weeks of age, the secreted immunoglobulin A (sIgA) content in the jejunum mucosa of the BA3 group was greater than the other groups (P < 0.001). Furthermore, altered intestinal microbiota was found in the BA3 group. Specifically, decreased amounts of Alistipes, Bacteroides, Odoribacter, Dehalobacterium, and Sutterella and increased amounts of Lactobacillus, Dorea, Ruminococcus, and Oscillospira were determined (P < 0.05) in the BA3 group at week 6. Meanwhile, decreased amounts of B. fragilis and C. leptum (P < 0.05) were identified in the BA3 group at week 12, which were found to be relevant for the improvement of intestinal morphology (P < 0.05) by Pearson analysis. In conclusion, simultaneous supplementation of AGP and B. subtilis for 0~3 weeks increased the relative abundance of beneficial microbiota in caecum in 0~6 weeks, then improved the intestinal morphology by elevating populations of B. fragilis and C. leptum in 7~16 weeks, and further upregulated sucrase expression and increased sIgA content in the intestinal mucosa in 13~16 weeks.